2013
DOI: 10.1159/000346244
|View full text |Cite
|
Sign up to set email alerts
|

Two Cases of Interferon-Alpha-Induced Sarcoidosis Koebnerized along Venous Drainage Lines: New Pathogenic Insights and Review of the Literature of Interferon-Induced Sarcoidosis

Abstract: Sarcoidosis is a systemic granulomatous disorder of unknown origin commonly affecting the lung, the lymphoid system and the skin. We report here two cases of cutaneous sarcoidosis in two former intravenous drug users following interferon (IFN)-α and ribavirin therapy for chronic hepatitis C. Both patients developed skin sarcoidosis along venous drainage lines of both forearms, coinciding with the areas of prior drug injections. The unique distribution of the skin lesions suggests that tissue damage induced by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 93 publications
0
15
0
1
Order By: Relevance
“…1 It commonly affects the lungs, lymphoid system, and skin. 2 Diagnosis is based on clinical presentation and histopathological findings. 3 Tumor necrosis factor is produced by inflammatory cells such as macrophages, keratinocytes, and T helper 1 (Th1) lymphocytes.…”
Section: Introductionmentioning
confidence: 99%
“…1 It commonly affects the lungs, lymphoid system, and skin. 2 Diagnosis is based on clinical presentation and histopathological findings. 3 Tumor necrosis factor is produced by inflammatory cells such as macrophages, keratinocytes, and T helper 1 (Th1) lymphocytes.…”
Section: Introductionmentioning
confidence: 99%
“…So, IFN therapy activated immune systems that help to eradicate HCV. The previous report indicated that IFN therapy for CHC triggered sarcoidosis via activating immune system [9][10][11] . Sarcoidosis is a granulomatous autoimmune disease of unknown etiology that may affect many organs.…”
Section: Discussionmentioning
confidence: 99%
“…54 In the cases of IFN-a-induced sarcoidosis koebnerized along venous drainage lines in former intravenous drug users, it was suggested that repeated venipuncture over several years resulted in tissue injury, chronic subclinical inflammation, and scar formation, which koebnerized the cutaneous sarcoidosis. 55 Sarcoidosis has been effectively treated with TNF-a blockers, owing to the important role of TNF-a in granuloma formation and maintenance. 56 However, there have also been case reports of an unexpected, paradoxic effect of the development of sarcoidosis in patients on anti-TNF-a therapy.…”
Section: Drug-induced Sarcoidosis Etiopathogenesismentioning
confidence: 99%
“…Interferon-a a, 54,55,63,65 Anti-TNF agents: etanercept, infliximab, adalimumab 57,58,60 Synthetic fillers used for cosmetic procedures (hyaluronic acid) 64 Zinc 80…”
Section: Box 4 Drugs That Induce Cutaneous Sarcoidosismentioning
confidence: 99%
See 1 more Smart Citation